Clinical Characteristics and Genetic Etiology of Children With Developmental Language Disorder - Plug, Marielle B.; van Wijngaarden, Vivian; de Wilde, Hester; van Binsbergen, Ellen; Stegeman, Inge; van den Boogaard, Marie-José H.; Smit, Adriana L. (Frontiers in Pediatrics, 2021)
Objective: Developmental language delay (DLD) is one of the most common disabilities in childhood and can negatively affect a child's communication skills and academic and/or psychosocial development. To date, an increasing number of causative genes have been identified by diagnostic techniques like next generation sequencing. An early genetic diagnosis is important to properly prepare and counsel children and parents for possible future difficulties. Despite this, genetic assessment is usually not part of a standardized diagnostic set in children with developmental language delay. In this study, we aim to assess the diagnostic outcomes of children primarily assessed for speech and language delay who were subsequently referred for genetic etiological assessment. Methods: Medical records of children referred to the department of Otorhinolaryngology of the Wilhelmina Children's Hospital for diagnostic work-up for a suspected speech and language delay between June 2011 and December 2018 who were additionally referred to a geneticist were evaluated. Study parameters concerning medical history, behavioral problems, language development, intelligence, and hearing were recorded. Outcomes of genetic analysis were evaluated. Results: A total of 127 patients were diagnosed with a developmental language delay. Genetic analysis was conducted in 119 out of 127 patients with a language delay and eligible for this study. The median time between initial speech and language assessment and the first genetic consultation was 10 months (IQR 5.0–23.0). In 34 out of 127 patients a causative genetic diagnosis was found to explain their DLD. Conclusion: In approximately a quarter of the patients (26.8%) diagnosed with developmental language delay, a causative genetic diagnosis was confirmed. This demonstrates the opportunity to identify an underlying genetic etiology in children with developmental language delay. However, in order to optimize the diagnostic process and clinical care for these children, two important research gaps need to be addressed. First, research should focus on assessing the clinical impact and effect on treatment outcomes of a genetic diagnosis. Secondly, it is important to recognize for which children genetic testing is most beneficial.